Beyond electrostatic modification: design and discovery of functional oxide phases via ionic-electronic doping. Issue 1 (1st January 2019) - Zhang, Hai-Tian; Zhang, Zhen; Zhou, Hua; Tanaka, Hidekazu; Fong, Dillon D.; Ramanathan, Shriram
ABSTRACT: A new research field of functional materials and device physics is rising that combines ionic transport with charge carrier modulation to realize emergent physical properties and discovery of metastable phases. The paradigm for enabling function extends far beyond carrier accumulation or depletion in band semiconductors or simply moving ions through an insulating electrolyte. Rather, by carefully selecting electronically or structurally fragile materials, one can collapse or open band gaps via extreme ionic dopant concentration, or reconfigure their entire crystal structure to create new phases. Electron–electron and electron–lattice interactions can be coupled or controlled independently in such systems via electric fields without thermal constraints by use of ionic dopants. The unifying theme across these studies is to introduce ions and electrons via electric fields through interfaces, with electrochemistry playing a dominant role. In this review, we briefly summarize this nascent field of iontronics and discuss principal results to date with examples from binary and complex oxides as well as selected 2D materials systems. We conclude the review by highlighting gaps in fundamental scientific understanding and prospects for the use of such novel devices in future electronic, photonic and energy technologies. Graphical Abstract: